A large-signal Pspice modeling of GaN-based MIS-HEMTs. (June 2019) - Liu, Chunyu; Wang, Xinhua; Huang, Sen; Ma, Xiaohua; Wang, Yuankun; Zhang, Sheng; Zhao, Rui; Shi, Wen; He, Quanbo; Yin, Haibo; Fan, Jie; Luo, Weijun; et al.
Abstract: In this work we present a physics-based semi-empirical large-signal model for GaN MIS-HEMTs, which introduces the non-segmented, smooth continuous equations to describe the static and dynamic characteristics of GaN MIS-HEMTs in different working regions. The unique physical effect of threshold voltage drift was considered for MIS-HEMTs in the current model, in addition to effects of the channel length modulation and the temperature drift. In addition, a current-controlled current source was used in the dynamic model to characterize the nonlinear capacitance including the gate-drain capacitance CGD, gate-source capacitance CGS and drain-source capacitance CDS at different operating voltages. The model is in excellent agreement with the experimental data for both drain current and capacitances over a typical range of applied voltages and temperatures.